Partisipasi Sosial Bank Pohon: Adaptasi Iklim dan Promosi Kesehatan - Fajriani Ananda; Yustikasari (JURNAL PROTEKSI KESEHATAN, 2026)
This qualitative case study examines social participation in the Tree Bank Program at the Faculty of Economics and Business, Universitas Riau, as a climate adaptation and campus health-promotion strategy. Existing green-campus studies largely emphasize physical infrastructure or environmental performance, while the social processes that sustain tree-based adaptation and health co-benefits remain underexplored. This study addresses that gap by integrating Cohen and Uphoff’s participation framework, social capital, and climate-health perspectives. Informants representing faculty leaders, lecturers, staff, students, alumni, Humendala, BPDAS, and DLHK were purposively selected. Data from interviews, observations, focus groups, and documents were thematically analyzed using NVivo 12 Plus. Participation was strongest in implementation, adequate in decision-making and benefit utilization, and weakest in evaluation. The study’s novelty lies in conceptualizing the Tree Bank as participatory green infrastructure whose adaptation and health value depends on maintenance, canopy growth, survival monitoring, heat-risk literacy, inclusive green-space use, and shared responsibility.